PENERAPAN PENDIDIKAN KARAKTER MELALUI EKSTRAKURIKULER TAPAK SUCI UNTUK MENINGKATKAN DISIPLIN DAN MINAT DI PESANTREN AT TAQWA MUHAMMADIYAH MIRI SRAGEN TAHUN AJARAN 2024/2025 - Pratama, Wildan Yoga; Hidayah, Nur (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study aims to: 1). Determine the implementation of character education through Tapak Suci extracurricular activities to enhance discipline and interest at Pesantren At Taqwa Muhammadiyah Miri Sragen in the 2024/2025 academic year. 2). Identify the supporting and inhibiting factors in implementing character education through extracurricular activities at Pesantren At Taqwa Muhammadiyah Miri Sragen in the 2024/2025 academic year. This research employs a qualitative approach. Data collection techniques include observation, interviews, and documentation. Data validity is ensured through triangulation of techniques and sources, while data analysis follows the stages of data collection, data reduction, and conclusion drawing. The findings of this study indicate that the implementation was carried out effectively. Several methods were employed in the Tapak Suci extracurricular activities to enhance discipline and interest. There are both supporting and inhibiting factors in implementing character education through Tapak Suci extracurricular activities at Pesantren At Taqwa Muhammadiyah Miri Sragen. Supporting factors include positive support from relevant stakeholders, commitment from students, support from parents, as well as adequate facilities and resources. However, some inhibiting factors were also identified, such as inconsistencies among trainers and the limited number of trainers, which may hinder the continuity of the program